2003
DOI: 10.1093/intimm/dxg015
|View full text |Cite
|
Sign up to set email alerts
|

CD4 T cell priming in dendritic cell-deficient mice

Abstract: Bone marrow (BM) chimeras (BMC) generated from mice carrying a null (-/-) mutation in the relB gene of the NF-kappaB family represent an ideal model for in vivo studies on the role of dendritic cells (DC) in the adaptive immune response. The spleen and lymph nodes (LN) of relB(-/-) BMC contain a small number of residual DC, mainly CD8alpha(+), that fail to up-regulate MHC class II and co-stimulatory molecules after stimulation in vitro. Moreover, residual spleen DC of relB(-/-) BMC have a 4-fold decrease in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 40 publications
2
14
1
Order By: Relevance
“…We found that Tg B lymphocytes failed to directly activate OVAspecific TCR-transgenic CD8 T cells (Fig. 3B), a result at variance with our previous report that OVA-specific TCR-transgenic CD8 T cells are readily activated by DC pulsed with OVA [21]. …”
Section: Differential Activation Of Cd4 and Cd8 T Cells By Antigen-prcontrasting
confidence: 98%
“…We found that Tg B lymphocytes failed to directly activate OVAspecific TCR-transgenic CD8 T cells (Fig. 3B), a result at variance with our previous report that OVA-specific TCR-transgenic CD8 T cells are readily activated by DC pulsed with OVA [21]. …”
Section: Differential Activation Of Cd4 and Cd8 T Cells By Antigen-prcontrasting
confidence: 98%
“…3). In agreement with data published elsewhere [22] the CD4 T cell response in relB -/-BM chimeras was also comparable to that measured in control C57BL/6 BM chimeras (stimulation index 7.6±0.8 vs. 9.8±2). These results suggest that CTL priming in the spleen in the model of somatic transgene immunization may occur in the absence of functional BM-derived DC.…”
Section: Ctl Priming In Vivo In Dc-deficient Micesupporting
confidence: 92%
“…However, because CTL priming was possible in relB -/-BM chimeras, whose spleen DC are unable to prime T cell responses to soluble antigen in vitro and in vivo [22], we argue that DC are dispensable in T cell priming in this model. Cross-priming can be ruled out on the basis of two additional considerations.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In relB Ϫ/Ϫ mice, deficient in myeloid and functional lymphoid DCs, CD4 ϩ T cells can be primed in response to soluble protein Ag, suggesting that B cells play a role in T cell priming in the absence of DC functions (54). In mice lacking B cells, primary CD4 ϩ or CD8 ϩ T cell priming can be generated (55).…”
Section: Discussionmentioning
confidence: 99%